Photocatalytic Abatement of Volatile Organic Compounds by TiO2 Nanoparticles Doped with Either Phosphorous or Zirconium - Melodj Dosa (Materials, 2019)
The aim of this work is to study the activity of novel TiO2-based photocatalysts doped with either phosphorus or zirconium under a UV-Vis source. A set of mesoporous catalysts was prepared by the direct synthesis: TiO2_A and TiO2_B (titanium oxide synthesized by two different procedures), P-TiO2 and Zr-TiO2 (binary oxides with either nonmetal or metal into the TiO2 framework). Complementary characterizations (N2 physisorption at 77 K, X-ray powder diffraction (XRD), field emission scanning electron microscopy (FESEM), energy dispersive X-ray (EDX) analysis, X-ray Photoelectron Spectroscopy (XPS), and (DR)UV-Vis spectroscopy) were used to investigate the physicochemical properties of the prepared catalysts. Then, the photocatalysts were tested for the oxidation of propylene and ethylene under UV-Vis light. As a result, the most promising catalyst for both the propylene and ethylene oxidation reactions was the P-TiO2 (propylene conversion = 27.8% and ethylene conversion = 13%, TOS = 3 h), thus confirming the beneficial effect of P-doping into the TiO2 framework on the photocatalytic activity.